Strategy for prevention of cancers of the esophagus. (29th September 2014) - Akiyama, Junichi; Alexandre, Leo; Baruah, Anushka; Buttar, Navtej; Chandra, Raghav; Clark, Allan B.; Hart, Andrew R.; Hawk, Ernest; Kandioler, Daniela; Kappel, Sonja; Krishnadath, Sheila K.; Sharma, Anamay; et al.
Abstract : The following, from the 12th OESO World Conference: Cancers of the Esophagus, includes commentaries on the animal reflux–inflammation models for Barrett's esophagus and esophageal adenocarcinoma; genomic/epigenomic analyses; eflornithine‐based combinations; the molecular derangements that promote neoplastic transformation; the role of COX‐2 inhibitors, proton pump inhibitors, and phase II trials in Barrett's adenocarcinoma; statins in chemoprevention and treatment of esophageal cancer; and biomarkers as potential targets in Barrett's adenocarcinoma.